Social capital as competitive resource - a driver towards sustained competitive advantage among manufacturing MSMEs in emerging markets - Vinayachandran, Vidya; Ambily, Ambilysadanam Soman (Serbian Journal of Management, 2020)
The strength of an emerging economy are the Micro, Small and Medium Enterprises as they paramount the economy to a greater extent. Since, MSMEs plays a greater role in the creation of wealth in advanced countries, there shall be justification on the less contribution of the same in developing economy. India as a developing economy should foster their industrial productivity and manufacturing MSMEs have a major role. It is being argued that the micro and small firms are exposed to sickness to a larger extent due to resource scarcity (Mehta & Rajan, 2017). The present study analyses social capital as a resource from structural social capital dimensions of MSMEs with respect to Government organizations and commercial banks for strengthening social capital of manufacturing MSMEs. The study is conducted based on 90 manufacturing MSMEs in Kerala.
Keywords: micro sector; small sector; medium sector; emerging economy; competitive resources; capabilities; social capital